Garlic and gaseous mediators - Rose, Peter; Moore, Philip Keith; Zhu, Yi-Zhun (Elsevier, 2018)
Garlic (Allium sativum) and allied plant species are rich sources of sulfur compounds. Major roles for garlic and its sulfur constituents include the regulation of vascular homeostasis and the control of metabolic systems linked to nutrient metabolism. Recent studies have indicated that some of these sulfur compounds, such as diallyl trisulfide (DATS), alter the levels of gaseous signalling molecules including nitric oxide (NO), hydrogen sulfide (H2S), and perhaps carbon monoxide (CO) in mammalian tissues. These gases are important in cellular processes associated with the cardiovascular system, inflammation, and neurological functions. Importantly, these studies build on the known biological effects of garlic and associated sulfur constituents. This review highlights our current understanding of the health benefits attributed to edible plants like garlic.